Case Study of Calculating Carbon Credits for Municipal Solid Waste Incineration Power Generation - Jie, Xinggang; Jie, Yinggang (International Journal of Natural Resources and Environmental Studies, 2024)
By replacing landfilling with municipal solid waste incineration, the emission of greenhouse gases (GHGs) generated by sanitary landfilling is avoided. Simultaneously, the thermal energy generated by waste incineration is utilized for power generation, replacing an equivalent amount of electricity generated from fossil fuels, thereby reducing greenhouse gas emissions. Taking a certain municipal solid waste incineration project as an example, relevant methodologies ACM0022 and CM-072-V01 are applied, and simulated calculations of Certified Emission Reductions (CCER) are conducted through national verification. Combined with the current carbon trading prices, additional value-added benefits are calculated, providing a reference for exploring growth opportunities for waste incineration power plants and achieving carbon peak and neutrality targets for the power plants.